Porous catalytic membranes for CO₂ conversion - Guo, Yi (2022)
Catalytic CO2 conversion has witnessed a dynamic growth in recent decades. Various materials have been applied to reduce CO2 into fuels and value-added chemicals. Normally, the powder-based catalysts cannot be directly utilized for CO2 conversion. Much attention was paid to the study of catalytic membranes in order to overcome this issue, since it is convenient for catalytic membranes to be employed in devices for practical applications. In this review, the recent research development of porous catalytic membranes for CO2 conversion is summarized. The preparations of representative porous catalytic membranes and their CO2 conversion methods, including electrocatalysis, photocatalysis, photoelectrocatalysis, thermalcatalysis and biocatalysis, are discussed in detail. This review is expected to provide deep understanding on the utilization of porous catalytic membranes for CO2 conversion.